Increase in Colorado Tick Fever Virus Disease Cases and Effect of COVID-19 Pandemic on Behaviors and Testing Practices, Montana, 2020 - Soto, Raymond A.; Baldry, Erika; Vahey, Grace M.; Lehman, Jennifer; Silver, Margaret; Panella, Amanda; Brault, Aaron C.; Hughes, Holly R.; Fitzpatrick, Kelly A.; Velez, Jason; Biggerstaff, Brad J.; Wolff, Brent; et al. (Emerging infectious diseases, 2023)
In 2020, Montana, USA, reported a large increase in Colorado tick fever (CTF) cases. To investigate potential causes of the increase, we conducted a case-control study of Montana residents who tested positive or negative for CTF during 2020, assessed healthcare providers' CTF awareness and testing practices, and reviewed CTF testing methods. Case-patients reported more time recreating outdoors on weekends, and all reported finding a tick on themselves before illness. No consistent changes were identified in provider practices. Previously, only CTF serologic testing was used in Montana. In 2020, because of SARS-CoV-2 testing needs, the state laboratory sent specimens for CTF testing to the Centers for Disease Control and Prevention, where more sensitive molecular methods are used. This change in testing probably increased the number of CTF cases detected. Molecular testing is optimal for CTF diagnosis during acute illness. Tick bite prevention measures should continue to be advised for persons doing outdoor activities.